The content in the messages of prevention of obesity that does not prevent health - Cruz-Licea, Verónica; Morales-García, María de Lourdes (Acta Universitaria, 2019)
In most prevention campaigns, it is not considered to measure the unexpected effect that they could have on the health of the population. The objective was to analyze the content of the messages of prevention campaigns of obesity that would have a negative effect on health. The content of the campaigns was examined with a qualitative technique of content analysis. It was found that the information in the messages is not clear enough and could lead to the practice of unhealthy behaviors. It was also observed that slender body images are presented as healthy along with negative stereotypes of obesity, which could damage the perception that people have of their body image. In conclusion, there are messages that, far from preventing obesity, would encourage body dissatisfaction and unhealthy behaviors such as dieting and an obsession to controlling and measuring body weight.